2009
DOI: 10.1175/2009mwr2933.1
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Typhoon Songda (2004) in Producing Distantly Located Heavy Rainfall in Japan*

Abstract: When Typhoon Songda (2004) was located southeast of Okinawa over the western North Pacific during 2-4 September 2004, a heavy rainfall event occurred over southern central Japan and its adjacent seas, more than 1200 km from the typhoon center. The Advanced Research version of the Weather Research and Forecast (WRF-ARW) model was used to investigate the possible remote effects of Typhoon Songda on this heavy precipitation event in Japan. The National Centers for Environmental Prediction (NCEP) global final (FNL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
83
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(94 citation statements)
references
References 33 publications
4
83
4
Order By: Relevance
“…(6) This case may fall under "intense rainfall remotely affected by TY" or "predecessor rain event of TY." However, the difference between this case and cases studied in previous articles (Wang et al 2009; Yoshida and Itoh 2012) indicated significant variety among "intense rainfall remotely affected by TY." Detailed studies for various cases are required to clarify the influence of the distantly located TY on the intense rainfall over Japan.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…(6) This case may fall under "intense rainfall remotely affected by TY" or "predecessor rain event of TY." However, the difference between this case and cases studied in previous articles (Wang et al 2009; Yoshida and Itoh 2012) indicated significant variety among "intense rainfall remotely affected by TY." Detailed studies for various cases are required to clarify the influence of the distantly located TY on the intense rainfall over Japan.…”
Section: Discussioncontrasting
confidence: 72%
“…Nagai and Fukatu (1967) studied the rainband by using the surface and radar observation data. Wang et al (2009) discussed the role of TY Songe on distantly located heavy rainfall in Japan on September 2̶4, 2004. When the TY was located southeast of Okinawa, a heavy rainfall of~250 mm occurred over south-central Japan on September 2̶4.…”
Section: Introductionmentioning
confidence: 99%
“…4a. The poleward transport of water vapor from TC Haima and poleward elongation of enhanced integrated water vapor toward the equatorward entrance region of an intensifying upper-tropospheric jet streak is consistent with the dynamics outlined for a possible predecessor rain event (PRE; e.g., Cote 2007;Wang et al 2009;Galarneau et al 2010;Byun and Lee 2012) over eastern China, South Korea, and Japan. Further analysis of the possible PRE is beyond the scope of the current investigation.…”
Section: Antecedent Upstream Conditionssupporting
confidence: 79%
“…Lately, attention has been paid to the enhanced poleward moisture transport that occurs often on the eastern side of a transitioning TC. When this moisture impinges on a midlatitude baroclinic zone in a region of upperlevel forcing for ascent [e.g., near the equatorward entrance region of an upper-level jet streak; Uccellini and Johnson (1979)] several days prior to ET, heavy precipitation and flooding may occur as a result of quasistationary convection in that region (e.g., Wang et al 2009;Galarneau et al 2010;Byun and Lee 2012;Schumacher and Galarneau 2012;Baek et al 2013). The associated weather system, called a predecessor rain event (PRE; e.g., Galarneau et al 2010;Bosart et al 2012;Moore et al 2013), tends to be located 500-2000 km away from the TC.…”
Section: Background On Tc-extratropical Flow Interactionmentioning
confidence: 99%